Faculty Time Allocation at Historically Black Universities and Its Relationship to Institutional Expectations - Escobar, Martha; Bell, Zebulon Kade; Qazi, Mohammed; Kotoye, Christian O.; Arcediano, Francisco (Frontiers in Psychology, 2021)
University faculty divide their time into their main academic responsibilities, typically identified as teaching, research, service and, at institutions with strong ties to their surrounding community, outreach. Most studies of time allocation have focused on faculty at Primarily White Institutions (PWI). The present study investigated how faculty at five Historically Black Universities (HBUs) allocate their time to their academic responsibilities. Data were analyzed based on their tenure status, gender, and representation in science, technology, engineering, and mathematics (STEM). Faculty estimated the percentage of time they currently allocate (current), the time they would ideally allocate (ideal), and the time they estimate their institution expects them to allocate (expected) to each academic responsibility. Across all demographics, there were discrepancies between current and ideal time allocation to research and teaching and, in some demographics, outreach. The greatest discrepancy between current and expected time allocation was observed in time allocated to research, with women and untenured faculty also showing a discrepancy in time allocated to teaching, and underrepresented faculty showing no discrepancies between current and expected time allocation. Women, untenured, and underrepresented faculty reported that their time allocation patterns were guided by external factors rather than personal preferences. The surveyed faculty also stated that the patterns of effort distribution expected to obtain tenure were not necessarily guided by the faculty handbooks at their institution. Although this study is limited by its relatively small sample size, it provides an insight into how faculty at HBUs divide their time and the reasons for them to do so.